Public Enthusiasm for Integrated Islamic Schools - Imron Rasyadi (Al-Hayat: Journal of Islamic Education, 2021)
This article aims to express the enthusiasm of the community (parents) to entrust their children to study at the Integrated Islamic School. Since the outbreak of the Integrated Islamic School, it has emerged amid the community that not only the existence of the school is in the province but has penetrated districts and cities in Indonesia. The author's observation is that the Integrated Islamic School is the main attraction for parents to entrust their children. Even in the last five years, this school has continued to increase the number of students who register. On this basis, the author is very interested in examining what factors attract parents to send their children to this school more deeply. This research is qualitative research that seeks to capture and translate the phenomena and facts related to the Integrated Islamic Elementary School (SDIT) Permata Hati Merangin Jambi with a descriptive-analytical method, which describes what findings were obtained based on interviews, observations and documentation, then analyzed using inductive and deductive theories so that the object of the research is well represented. The results found are the enthusiastic factors of the community (parents) entrusting their children to the Integrated Islamic School, namely (1) the integration of the Religious Education curriculum with general education; it is implemented and not just a mere slogan; (2) Integrated Islamic School Implementing a full day school learning system, because this model system has many benefits, especially respect for time, and (3) Parents are personally involved actively in guiding children to learn.